Synchronous polyps predict metachronous colorectal lesions after curative resection of colorectal cancer. Issue 4 (3rd July 2016) - Pozza, Anna; Ruffolo, Cesare; Fiorot, Alain; Padoan, Luigi; Erroi, Francesca; Massani, Marco; Caratozzolo, Ezio; Bonariol, Luca; Ferrara, Francesco; Norberto, Lorenzo; Castoro, Carlo; Bassi, Nicolò; et al.
Abstract: Background: The principal aim of endoscopic follow-up programs after curative resection of colorectal cancer (CRC) is to improve survival and identify local recurrence and metachronous CRC. The aim of our study was to identify the possible predictors of metachronous colorectal lesions. Methods: The records of 348 consecutive patients with CRC and who completed at least 1 year of endoscopic follow-up after surgery were analyzed. In this group, 336 patients underwent surgery for primitive CRC and 12 for metachronous cancer. Patients' characteristics, operative details, and endoscopical follow-up findings were retrieved. Multivariate survival analyses were used to identify patient categories at risk of metachronous colonic lesions. Results: 128 patients presented a metachronous lesion: 118 adenomas and 10 adenocarcinomas. At multivariate analysis, active smoke (HR = 1.84, p  = 0.03), neoadjuvant therapy (HR = 0.24, p  = 0.01), and presence of synchronous polyps (HR = 1.55, p  = 0.04) resulted independent predictors of metachronous adenoma after CRC removal while neoadjuvant therapy (HR = 0.25, p  = 0.02), active smoke (HR = 1.54, p  = 0.04), and presence of synchronous polyps (HR = 1.86, p  = 0.02) resulted independent predictors of metachronous lesions after CRC removal. Conclusions: This study demonstrated a high rate of metachronous lesions in the early follow-up after curative CRC resection. The negative effects of synchronous polyps should be carefully evaluated when planning patients' follow-up.